Analysis of the Triggering Factors of Heavy Rainfall on Geological Disasters - Zhao, Wenbin (International Journal of Natural Resources and Environmental Studies, 2026)
Against the backdrop of global climate warming and intensified human activities, geological hazards triggered by heavy rainfall pose an increasingly prominent threat to the regional ecological environment as well as to human life and property. Taking Huixian City, Henan Province, as the study area, this paper systematically investigates the triggering factors and mechanisms of geological hazards induced by heavy rainfall through a combination of literature review, field sampling, and laboratory testing. First, the geological environmental conditions of Huixian City, including topography, stratigraphy and lithology, and meteorological-hydrological characteristics, were reviewed. Second, the physical and mechanical properties of typical silty clay in the study area were analyzed through direct shear tests and soil-water characteristic curve tests. The results show that the geological hazards in the area are mainly small- and medium-scale collapses, landslides, and debris flows, which are concentrated in low- to middle-mountainous and hilly areas and are highly consistent with heavy rainfall during the flood season (June to October) in both temporal and spatial distribution. The shear strength first increases and then decreases with increasing water content, cohesion reaches its peak at the optimum water content, and matric suction is significantly negatively correlated with water content. Finally, the core mechanism is clarified: heavy rainfall increases the water content of rock and soil masses, softens the rock-soil structure, and reduces the shear strength of the rock mass, thereby triggering geological hazards. The results of this study can provide a scientific basis and technical support for the monitoring, early warning, prevention, and control of geological hazards in Huixian City and other areas prone to similar geological hazards.